Management of Cerebral Aneurysm Descriptors based on an Automatic Ostium Extraction - Meuschke, Monique; Günther, Tobias; Wickenhofer, Ralph; Gross, Markus; Preim, Bernhard; Lawonn, Kai (IEEE Computer Graphics and Applications, 2018)
We present a framework to manage cerebral aneurysms. Rupture risk evaluation is based on manually extracted descriptors, which is time-consuming. Thus, we provide an automatic solution by considering several questions: How can expert knowledge be integrated? How should meta data be defined? Which interaction techniques are needed for data exploration.
CRIS-Team Scopus Importer:2020-09-23
Keywords: cerebral aneurysms; computer graphics; data management; morphological descriptors; ostium extraction; visualization